Darkness of man [videorecording (DVD)] - Bressack, James Cullen; Cho, Alethea; Damme, Jean-Claude van, 1960-; Damme, Jean-Claude van, 1960-; Loken, Kristanna, 1979-; Min, Emerson; Breslin, Spencer; Sticky Fingaz (Rapper); Doherty, Shannen; Jones, Timothy Stuart; Sale, James T. (Sony Pictures Home Entertainment, 2024)
Former Interpol operative Russell Hatch must protect an informant's son who is in the middle of a turf war between street gangs.